The Arab-Israeli conflict in Israeli history textbooks, 1948-2000 - Podeh, Elie (Bergin & Garvey, 2002)
Israeli history textbooks in the past contained many biases, distortions, and omissions concerning the depiction of Arabs and the history of the Arab-Israeli conflict. Today these misrepresentations are gradually being corrected. By reviewing curricula and textbooks used in the Israeli educational system since the establishment of Isreal, the author shows how the Israeli educational system, and particularly history textbooks, have presented the image of the Arab and the history of Arab-Israeli relations in the years from 1948 to 2000, and how the trend is to provide a more balanced portrait of the other side. encourages the depiction of a balanced portrait in all textbooks.